A DEIXIS ANALYSIS OF THE SONG LYRICS DYNAMITE PERFORMED BY BANGTAN SONYEONDAN - caca, cahaya ayu anisa (Center of Language and Cultural Studies [CLCS], 2024)
This study aimed to analyze the types of deixis found in the song lyrics of Dynamite by Bangtan Sonyeondan and the function of the deixis, which was used in the song lyrics of Dynamite performed by Bangtan Sonyeondan. This research used the deixis theory from George Yule. The researcher used a descriptive-qualitative method through library research. The song lyrics for Dynamite, performed by Bangtan Sonyeondan, were the basis of this research. The data collection was downloaded from the internet, and it was analyzed by listening to a song, reading the script of the song lyrics, and identifying, classifying, and drawing conclusions. The findings of the study showed that the researcher found that there are 3 types of deixis, namely person deixis, spatial deixis, and temporal deixis. The appearance frequency of person deixis is 51 times, while spatial deixis is 17 times, and temporal deixis is 14 times. The function of person deixis is more directed at indicating or mentioning the person. In addition, there are indications of repetition of the use of the noun in the song lyric line; through pragmatic analysis, it turns out that the repetition of the word has a different meaning.